Strategi Promosi Pendidikan di SDN 8 Talang Kelapa dalam Meningkatkan Minat Peserta Didik Baru - Marini Sapitri; Ade Akhmad Saputra; Rabial Kanada (JURNAL ILMIAH NUSANTARA, 2026)
Education has become an increasingly competitive sector, requiring institutions to implement strategic marketing management to maintain public trust. This study aims to describe and analyze the educational promotion strategies at SDN 8 Talang Kelapa in an effort to increase the interest of new students. The research employs a qualitative approach with a case study method. Data were collected through the human instrument, supported by interview guides, non-participant observation, and documentation of school publication materials. Primary data sources involved the School Principal and the New Student Admission (PPDB) committee, while secondary data sources involved parents. Data analysis was conducted systematically through the cycles of collection, reduction, data display, and conclusion drawing based on the Miles & Huberman model (1994). The results indicate that the implemented promotion strategies encompass a mix of direct promotion, such as visits to local kindergartens, and indirect promotion through the utilization of digital and print media. The success of these strategies is significantly influenced by the role of public relations management in building a positive school image and effectively communicating the superiority of facilities and educational programs. This study concludes that structured and technologically adaptive promotion strategies are crucial in enhancing school visibility and attractiveness amidst competition between educational institutions.